CD155 as a prognostic and predictive biomarker in acute myeloid leukemia - Ashraf Zeidan Abdalla; Salah Mabrouk Khallaf; Asmaa Mohammed Zahran; Nehal Adel Rayan; Ahmed Refaat Abd Elzaher (Discover Oncology)
Abstract Background Acute myeloid leukemia (AML) is a heterogeneous hematological malignancy with different molecular and genetic alterations. CD155 is expressed on myeloid cells and serves as a recognition molecule for natural killer (NK) cells to induce cytotoxicity. This study aimed to assess the prognostic and predictive value of CD155 in patients with AML. Methods We studied the expression of CD155 via flow cytometry in 93 AML patients at initial diagnosis at the Medical Oncology Department, South Egypt Cancer Institute (SECI), Egypt. Results Flow cytometry revealed that a mean fluorescence intensity ratio (MFIR) ≥2.68 was associated with high CD155 expression. This criterion was met in 62 patients (66.7%). High expression was associated with a worse composite complete remission (CRc) rate than low expression (29.0 vs. 54.8%; P = 0.015). High CD155 expression had significantly shorter relapse-free survival (RFS), with a median of 1.68 (95% CI 0.92–2.43) months (P = 0.015), and overall survival (OS), with a median of 1.68 (95% CI 0.74–2.88) months (P = 0.041). Conclusions High expression of CD155 in adult patients with AML is associated with a lower CRc, shorter RFS, and OS. It could be included within the predictive and prognostic panels.